Über die Bereiche der gleichmässigen Konvergenz der Newtonschen Reihe und der Fakultatenreihe - Morosjuk, E. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. В. Морозюк. Об областях равномерной сходимости рядов Ньютона и факториального E. Moroziuk. Niutono ir faktorialinių eilučių tolygios konvergencijos sritys